The Effect of Telang Flower Extract (Clitoria Ternatea) on Reducing Total Cholesterol Levels in Male Wistar Rats (Rattus Norvegicus) with Obesity - Haryati, Aprillia Sri; Tanamal, Claudia; Pratomo, Fransiskus Aryo (International Journal of Public Health Excellence (IJPHE), 2024)
Several health problems can arise from obesity, including an increased risk of diabetes mellitus, heart disease, high blood pressure, and high cholesterol. High cholesterol levels are associated with obesity, which is a health risk in and of itself. Achieving excellent health requires careful monitoring of cholesterol levels, and one way to do this is to eat foods rich in antioxidants. Specifically, this study used a laboratory experimental design, a true of experimental quantitative research. The research used twenty-four male Wistar rats (Rattus norvegicus). This study set out to compare the pre-and post-administration of Telang flower extract (Clitoria ternatea) to total cholesterol levels in the blood of rats (Rattus norvegicus). The tests were administered for homogeneity, one-way ANOVA, and normality. After that, SPSS was used to examine the study data. Researchers observed that compared to other methods, a 600mg/KgBW dose of butterfly pea flower extract (Clitoria ternatea) significantly reduced total cholesterol levels in obese male Wistar rats (Rattus norvegicus) from 65.06mg/dl to 37.46mg/dl. The study found that the phytochemical content of Telang flowers helped obese people lower their cholesterol levels.